MANAGERIAL CAPABILITIES AND CORPORATE PERFORMANCE OF INSURANCE FIRMS IN NIGERIA - Oloda, Oluwatayo Felix (European Science Publishing, 2025)
This study examines the relationship between managerial capabilities and corporate performance in insurance firms in Nigeria, with a particular focus on the moderating role of technology. Specifically, the research explores how managerial cognitive capabilities and managerial human capital influence operational efficiency and growth in customer base. Adopting a correlational research design, data were collected from 112 senior management personnel of insurance firms using a structured questionnaire. The findings reveal significant positive relationships between managerial cognitive capabilities and operational efficiency (r = .852, p < .01) as well as growth in customer base (r = .753, p < .01). Similarly, managerial human capital showed strong positive correlations with operational efficiency (r = .693, p < .01) and growth in customer base (r = .705, p < .01). Furthermore, the results indicate that technology significantly moderates the relationship between managerial capabilities and corporate performance, as evidenced by a reduction in the correlation coefficient from .682 to .594 when technology is introduced. This suggests that while managerial capabilities are crucial for enhancing corporate performance, the integration of technology further strengthens this relationship by optimizing operational processes and improving efficiency. The study concludes by recommending targeted investments in managerial training, strategic technological adoption, and digital transformation initiatives to address inefficiencies and drive sustainable growth in the Nigerian insurance sector.
Keywords: Managerial Capabilities. Corporate Performance. Managerial Cognitive Capabilities. Managerial Human Capital. Operational Efficiency. Growth In Customer Base. Technology. Nigerian Insurance Firms.